2020
DOI: 10.3390/rs12020240
|View full text |Cite
|
Sign up to set email alerts
|

Ground and Volume Decomposition as a Proxy for AGB from P-Band SAR Data

Abstract: In this work, the role of volume scattering obtained from ground and volume decomposition of P-band synthetic aperture radar (SAR) data as a proxy for biomass is investigated. The analysis here presented originates from the BIOMASS L2 activities, part of which were focused on strengthening the physical foundations of the SAR-based retrieval of forest above-ground biomass (AGB). A critical analysis of the observed strong correlation between tomographic intensity and AGB is done in order to propose simplified AG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…At present, the four primary techniques used to enhance the accuracy of AGB estimates are (i) the synthetic aperture radar technique (Montesano et al, 2013(Montesano et al, , 2014, (ii) the laser intensity direction and ranging (LiDAR) technique (Cao et al, 2018;Hu et al, 2020), (iii) the narrowband hyperspectral technique (Filippi et al, 2014;Tao et al, 2020), and (iv) the crop-height model (CHM; Roth and Streit, 2018;Zhu et al, 2019a;Issa et al, 2020). Given the use of long-wavelength electromagnetic radiation, synthetic aperture radar remote-sensing techniques can penetrate the crop canopy and are not affected by weather conditions, which means that they overcome the problem of premature saturation of AGB estimates by optical remote-sensing VIs and are thus highly suitable for long-term monitoring of AGB for areas with high crop coverage (Banda and Tebaldini, 2020). Previous studies have confirmed that using the backscattering coefficient of synthetic aperture radar remote sensing produces highly accurate estimates of crop AGB for wheat (Han et al, 2019), maize (Hosseini et al, 2019), and rice (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the four primary techniques used to enhance the accuracy of AGB estimates are (i) the synthetic aperture radar technique (Montesano et al, 2013(Montesano et al, , 2014, (ii) the laser intensity direction and ranging (LiDAR) technique (Cao et al, 2018;Hu et al, 2020), (iii) the narrowband hyperspectral technique (Filippi et al, 2014;Tao et al, 2020), and (iv) the crop-height model (CHM; Roth and Streit, 2018;Zhu et al, 2019a;Issa et al, 2020). Given the use of long-wavelength electromagnetic radiation, synthetic aperture radar remote-sensing techniques can penetrate the crop canopy and are not affected by weather conditions, which means that they overcome the problem of premature saturation of AGB estimates by optical remote-sensing VIs and are thus highly suitable for long-term monitoring of AGB for areas with high crop coverage (Banda and Tebaldini, 2020). Previous studies have confirmed that using the backscattering coefficient of synthetic aperture radar remote sensing produces highly accurate estimates of crop AGB for wheat (Han et al, 2019), maize (Hosseini et al, 2019), and rice (Yang et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Given the use of long-wavelength electromagnetic radiation, synthetic aperture radar remote-sensing techniques can penetrate the crop canopy and are not affected by weather conditions, which means that they overcome the problem of premature saturation of AGB estimates by optical remote-sensing VIs and are thus highly suitable for long-term monitoring of AGB for areas with high crop coverage ( Banda and Tebaldini, 2020 ). Previous studies have confirmed that using the backscattering coefficient of synthetic aperture radar remote sensing produces highly accurate estimates of crop AGB for wheat ( Han et al, 2019 ), maize ( Hosseini et al, 2019 ), and rice ( Yang et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Volume separation can be obtained through model-based ground and volume decomposition techniques [33,34], although the decomposition does not have a unique solution and the preferred solution is obtained by imposing physical constraints on the model [35,36]. Interferometric ground cancellation [37] instead relies purely on geometry.…”
Section: Agb Retrievalmentioning
confidence: 99%
“…When an electromagnetic wave passes from one medium to another, changing, therefore, refraction index, or when it strikes an object such as a radar target and it is reflected, it allows a polarization control to acquire knowledge of the characteristic information about the reflectivity, e.g., the orientation and shape of the reflecting object. In classical radars, i.e., amplitude-only radars, the information about a target is mainly obtained from the energy of the returned pulse; interferometric SAR exploits fully the phase and Doppler information, but not the polarization information of the electromagnetic vector wave-scatterer interrogation process [116][117][118][119].…”
Section: Scattering Mechanisms and Radar Observatory Techniquesmentioning
confidence: 99%